Fiscal Union in Europe? Efficiency, Equity and Stabilizing Effects of an EU-Wide Income Tax - Dirk Neumann; Olivier Bargain; Mathias Dolls; Clemens Fuest; Andreas Peichl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
One central lesson of the sovereign debt crisis is that the Eurozone (and the EU) needs institutional reform. Many observers argue that the monetary union should be complemented by a fiscal union . In this paper we provide the first quantitative analysis of important economic effects of an EU income tax. Using the European tax-benefit calculator EUROMOD, we simulate detailed individual budget curves in order to estimate an average EU tax system . Three key issues are analyzed: firstly, we assess the direct distributional implications of an EU tax (partly) replacing national tax systems. Applying different voting schemes, we especially investigate whether such a step could find political support in each country and the EU as a whole. Secondly, by using behavioral simulation techniques we analyze the impact of introducing a common tax on economic efficiency and adjust the distributional effects accordingly. Thirdly, we investigate the potential of an EU income tax to act as an automatic fiscal stabilizer in the event of an asymmetric shock. We derive crucial policy implications from our simulation exercise for the reform of the Eurozone and shed some light on a very important set of questions: How would further fiscal integration economically affect different households in the different member states? How would it affect automatic stabilizers in the EU?
Keywords: H20; H31; J22; 330